2003
DOI: 10.1080/02841860310013346
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Overview of Radiation Therapy Effects in Hodgkin's Lymphoma

Abstract: A systematic review of radiation therapy trials in several tumour types was carried out by The Swedish Council of Technology Assessment in Health Care (SBU). The procedures for evaluation of the scientific literature are described separately (Acta Oncol 2003; 42: 357-365). This synthesis of the literature on radiation therapy for Hodgkin's lymphoma (HL) is based on data from 12 randomized trials and 2 meta-analyses. Data from 3 prospective studies, 29 retrospective studies and 58 other articles were also used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…44 Reductions in radiotherapy field sizes and treatment doses for HL and NHL have been made to address the known increased risks for second cancers and cardiac complications caused by radiotherapy. [45][46][47] It is only very recently, however, that epidemiology studies have shown associations between mesothelioma and radiation treatment for NHL and testicular cancer. 7,19 Travis et al 7 used SEER data through 2001, enhanced by data from other population-based registries in Canada and Europe, to identify 40,576 survivors of testicular cancer who were followed for second cancers.…”
Section: Discussionmentioning
confidence: 99%
“…44 Reductions in radiotherapy field sizes and treatment doses for HL and NHL have been made to address the known increased risks for second cancers and cardiac complications caused by radiotherapy. [45][46][47] It is only very recently, however, that epidemiology studies have shown associations between mesothelioma and radiation treatment for NHL and testicular cancer. 7,19 Travis et al 7 used SEER data through 2001, enhanced by data from other population-based registries in Canada and Europe, to identify 40,576 survivors of testicular cancer who were followed for second cancers.…”
Section: Discussionmentioning
confidence: 99%
“…7,22,23 Two recent large cohort studies from the Netherlands and UK show an increased standardized mortality rate in CVD that is probably attributed to radiotherapy and adriamycin. 5,4 The UK study also found a significant relation to vincristin.…”
Section: Discussionmentioning
confidence: 99%
“…It was not then until early 1960's when extended field RT (EF-RT) was adopted as standard of care for early stage HL. However, EF-RT was complicated by high relapse rates (Horwich, Specht & Ashley, 1997) and serious long-term side effects including pulmonary dysfunction, heart disease and secondary cancers (Gustavsson, Osterman & Cavallin-Stahl, 2003). Hence, in an attempt to lessen toxicity and improve treatment outcomes, several studies over the past 3 decades addressed those concerns through modifying the radiation field/dose and/or incorporating chemotherapy to RT.…”
Section: Radiotherapy Alonementioning
confidence: 99%